RELATIONSHIP OF WORK STATUS WITH COMPLETENESS OF BASIC IMMUNIZATION IN INFANTS IN THE WORKING AREA OF THE PUSKESMAS BOTANIA - Ferry Daniel Martinus Sihombing; Omar Sazaly Aldy (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Background :In Indonesia experienced a very worrying Extraordinary Event (KLB), namely the incidence of Diphtheria. Diphtheria incidence in Indonesia has always fluctuated since the 1980s. In 2007 there were 183 cases of diphtheria which increased to 1,192 cases in 2012 and decreased incidence of diphtheria in 2013-2016 (Sariadji, 2017). And according to the Indonesian Pediatrician Association (IDAI), the diphtheria outbreak in Indonesia is the highest in the world. Diphtheria outbreaks occurred in 28 provinces and 142 districts / cities. So there has never been the most in the world and the coverage is 28 Provinces, "said the Chairman of the Indonesian Pediatrician Association, Aman Bhakti Pulungan, during a press conference at the IDI office Jalan Sam Ratulangi, Central Jakarta (Nugraha, 2017). As of November 2017, there were 20. provinces that have reported diphtheria with 593 cases and 32 deaths. Director General of Disease Prevention and Control Ministry of Health, Mohamad Subuh said, 66 percent of the total prevalence did not immunize. Then, 31 percent did immunization, but not until the final stage. To be free from diphtheria, at least the individual must get three times the immunization. Meanwhile, the remaining 3 percent has received complete immunization (Putra, 2017). The purpose of this study is the relationship between work status and completeness of basic immunization in infants. Method : quantitative with cross sectional approach. Research location Pus public health Botania. The population in this study were all live births in the Botania Community Health Center working area, namely 2184 people. This sampling technique uses purposive sampling method, data analysis uses bivariate data analysis with statistical tests, namely the Chi Square test using the SPSS program. Result : shows that out of 96 respondents the majority have a working status of work as many as 54 people (56.2%), majority were incomplete as many as 56 people (58.3%). Chi-square analysis results obtained p-value 0.000, which means p-value <0.05 so that Ho is rejected